PENERAPAN PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERIENERGI BUNYI - sofi chairunnisa; Nisrinda Nasywa Tsuraya; Vindika Rahayu Wilujeng; Wahyu Kurniawati (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2023)
Based  on  observation  conducted  at  SDN  Ngadirejo  II  Rengel  Tuban,  the researcher  found  that  the  learning  process  is  still  less  effective.  The  students  had difficulty  in  understanding    the  science  material  aboutthe  energy  of  sound.  It  is caused  by  several  factors,  one  of  which  is  the  informtion  transfer  just  use  the  direct instruction  method,  the  Students  opportunity  to  develop  the  skills  to  ask  and  submit answers  are  still  lacking,  so  that  student  learning  outcomes  under  KKM.  Therefore, the  researcher  applied  the  science  process  skills  approach  to  improving  classroom student learning outcomes. This research used the Classroom Action Research (CAR) as  its  design,  which  is  each  cycle  consists  of  four  phases:  planning,  implementation, observation, and reflection. the research Subjects were students in the fourth grade in SDN II Ngadirejo Rengel Tuban, which has 21 students. Data collecting technique is done through tests of learning outcomes with achievement test sheet instruments. The indicators of the successfullness of the study are measured through the percentage of individual completeness and classroom. The results showed that the students' learning outcomes  increased  with  the  percentage  of  classical  completeness  by  42,85%  in  pre-study  to  66,67%  in  the  first  cycle  and  95,23%  in  the  second  cycle.  The  obstacle encountered  in  the  study  was  that  the  teachers  and  students  at SDN  Ngadirejo  II Rengel Tuban were not used to apply the science process skills approach.